Impact of Lifestyle Interventions on Cardiovascular Risk Factors in Patients with Metabolic Syndrome - Faiz Ullah,; Atiq Ur Rehman,; Khan, Rahim Dil; Mahmood, Ijaz; Khan, Ajmal; Khan, Khushal (Indus Journal of Bioscience Research, 2025)
Introduction: Metabolic syndrome is a growing public health concern, characterized by a cluster of cardiovascular risk factors including central obesity, hypertension, dyslipidemia, and impaired glucose regulation. Lifestyle interventions have shown promise in improving these parameters. Objective: To evaluate the impact of lifestyle interventions on cardiovascular risk factors in patients diagnosed with metabolic syndrome. Materials and Method: A six-month interventional study was conducted at Department of Cardiology, Hayatabad Medical Complex Peshawar, Pakistan from July, 2024 to December, 2024. One hundred adult patients with metabolic syndrome were enrolled. Lifestyle modifications included dietary counseling, physical activity, and behavioral support. Anthropometric and biochemical parameters were assessed at baseline and after intervention. Results: Participants showed significant reductions in waist circumference, blood pressure, fasting glucose, and triglycerides, along with an increase in HDL cholesterol. By study end, 36% of patients no longer met the criteria for metabolic syndrome. Conclusion: Structured lifestyle interventions effectively reduce cardiovascular risk factors and can reverse metabolic syndrome in a significant proportion of patients.